HOW DOES DIGITAL TRANSFORMATION MEDIATE OF PRICE AND PROMOTION IN INFLUENCING ONLINE TRAIN TICKET PURCHASING DECISIONS? - Mahmud, Muhamad Farid; Tesniwati, Rini; Istiqomah, Istiqomah (Universitas Gunadarma, 2025)
The ease of digital markets in mediating and bridging train ticket reservations has become an interesting phenomenon in Indonesia, consumers are increasingly interested in exploring online platforms because of their ease of use and variety. This study examines how digital transformation mediates the impact of pricing and advertising on online rail ticket purchases. Employing the Structural Equation Model approach to investigate the link between latent variables, we find that digital transformation strengthens consumer decision-making by making pricing strategies more transparent and accessible. These findings provide insights for businesses to improve their digital strategies.